Bridging cultural differences in the global corporate environment - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
People form cultural biases from a young age, and this is something that we carry into our adult lives, as members of society, parents, employers and employees. Globalisation has, however, connected familiar and unfamiliar cultures – and people may be ill-prepared to manage their biases. It is not unusual today, for instance, to expect that many jobs will involve some form of interaction with a non-local. So, according to Natalie Turner, the CEO and founder of a multinational consultancy, organisations that give greater attention to bridging cultural gaps will reap greater efficiencies.